Peran Organisasi Kerjasama Islam (OKI) dalam Penguatan Diplomasi Islam - Cantika Niscala Puri; Gonda Yumitro (Faculty of Social and Political Sciences, Universitas Muhammadiyah Malang, 2022)
Diplomacy is commonly understood as a country's art, practice, and negotiation activity to advance that country's interests. Currently, conventional diplomacy is being practised, which is seen as having many flaws. Conventional diplomacy appears relatively unclean, so it is necessary to build and strengthen clean diplomacy based on an Islamic perspective, also known as Islamic Diplomacy. The OIC's Islamic diplomacy is very different from conventional diplomacy, which has flaws and is relatively dirty in its execution. This article attempts to analyze the role of the Organization of Islamic Cooperation in strengthening Islamic diplomacy using a descriptive qualitative approach. Islamic diplomacy, which prioritizes peace and cooperation to solve problems, is deemed appropriate to protect and defend Muslims' vital interests and to find solutions to conflicts. The authors also found that the OIC plays two essential roles in strengthening Islamic diplomacy. First, by prioritizing cooperation and peace, the OIC optimizes diplomacy. Second, diplomacy focuses on conflict prevention and resolution. This finding could be an alternative to developing Islamic diplomacy as another way of international relations.